2016
DOI: 10.1118/1.4941362
|View full text |Cite
|
Sign up to set email alerts
|

Technical Note: Compact three‐tesla magnetic resonance imager with high‐performance gradients passes ACR image quality and acoustic noise tests

Abstract: The compact system simultaneously allows for high gradient amplitude and high slew rate. Geometric distortion concerns have been mitigated by extending the spherical harmonic correction to higher orders. Acoustic noise is within the FDA limits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
30
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 25 publications
0
30
0
Order By: Relevance
“…For example, when imaging the head, body GCs still produce a high amplitude of time-varying magnetic fields over the entire torso cross-section, which causes PNS without improving imaging quality. The advantage of smaller-sized GCs with a reduced linearity region diameter is that fields are limited primarily to the head, decreasing the amplitudes of time-varying electric fields and induced currents significantly, thereby increasing PNS thresholds substantially (Wade et al, 2016; Tan et al, 2016; Weavers et al, 2016). This permits even higher useable gradient performance than expected from hardware specifications alone, compared to body-sized gradient coils.…”
Section: Dedicated Gradient Concepts Suitable For Uhfmentioning
confidence: 99%
“…For example, when imaging the head, body GCs still produce a high amplitude of time-varying magnetic fields over the entire torso cross-section, which causes PNS without improving imaging quality. The advantage of smaller-sized GCs with a reduced linearity region diameter is that fields are limited primarily to the head, decreasing the amplitudes of time-varying electric fields and induced currents significantly, thereby increasing PNS thresholds substantially (Wade et al, 2016; Tan et al, 2016; Weavers et al, 2016). This permits even higher useable gradient performance than expected from hardware specifications alone, compared to body-sized gradient coils.…”
Section: Dedicated Gradient Concepts Suitable For Uhfmentioning
confidence: 99%
“…Systems assessments of gradient linearity, PNS, and acoustic sound pressure levels were performed and the results were reported previously . To summarize, the results indicated that the 10th‐order spherical harmonic correction with both even and odd terms resulted in a residual RMS error of less than 0.36 mm .…”
Section: Resultsmentioning
confidence: 71%
“…A novel, compact 3T MR scanner (C3T) was developed as a technology demonstrator under a National Institutes of Health (NIH)‐funded program. The motivation behind the C3T was to demonstrate the advantages offered by a lightweight, low‐cost, and high‐performance MR system.…”
mentioning
confidence: 99%
“…The C3T was designed with a high‐performance gradient system with a 42‐cm inner diameter. Due to its relatively small size, the gradient system can achieve 80 mT/m amplitude and 700 T/m/s slew rate simultaneously, while remaining below the peripheral nerve stimulation limit . To facilitate patient access, it was necessary to shift the imaging volume towards the patient end of the bore to accommodate both the head and shoulder.…”
mentioning
confidence: 99%